Validating clinical practice guidelines for the management of febrile infants presenting to the emergency department in the UK and Ireland. Issue 4 (16th September 2021) - Waterfield, Thomas; Lyttle, Mark D; Munday, Charlotte; Foster, Steven; McNulty, Marc; Platt, Rebecca; Barrett, Michael; Rogers, Emma; Durnin, Sheena; Jameel, Nida; Maney, Julie-Ann; McGinn, Claire; et al.
Abstract : Objective: To report the performance of clinical practice guidelines (CPG) in the diagnosis of serious/invasive bacterial infections (SBI/IBI) in infants presenting with a fever to emergency care in the UK and Ireland. Two CPGs were from the National Institutes for Health and Care Excellence (NICE guidelines NG51 and NG143) and one was from the British Society for Antimicrobial Chemotherapy (BSAC). Design: Retrospective multicentre cohort study. Patients: Febrile infants aged 90 days or less attending between the 31 August 2018 to 1 September 2019. Main outcome measures: The sensitivity, specificity and predictive values of CPGs in identifying SBI and IBI. Setting: Six paediatric Emergency Departments in the UK/Ireland. Results: 555 participants were included in the analysis. The median age was 53 days (IQR 32 to 70), 447 (81%) underwent blood testing and 421 (76%) received parenteral antibiotics. There were five participants with bacterial meningitis (1%), seven with bacteraemia (1%) and 66 (12%) with urinary tract infections. The NICE NG51 CPG was the most sensitive: 1.00 (95% CI 0.95 to 1.00). This was significantly more sensitive than NICE NG143: 0.91 (95% CI 0.82 to 0.96, p=0.0233) and BSAC: 0.82 (95% 0.72 to 0.90, p=0.0005). NICE NG51 was the least specific 0.0 (95% CI 0.0 to 0.01), and this was significantly lower than the NICE NG143: 0.09 (95% CI 0.07 to 0.12, p<0.0001) and BSAC: 0.14 (95% CI 0.1 to 0.17, p<0.0001). Conclusion: None of the studied CPGs demonstrated ideal performance characteristics. CPGs should be improved to guide initial clinical decision making. Trial registration number: NCT04196192 . Abstract : This retrospective cohort study assessed the performance of Clinical Practice Guidelines (CPG) in the diagnosis of serious bacterial infections in infants with fever in the UK /Ireland and found that no CPG performed in an ideal manner, suggesting the need for further study.